A papilloma in a large cyst of the breast: A case report. (2019) - Kim, Hwan Soo; Kim, Yang Hei; Park, Sung Bae
Highlights: Intracystic lesions of the breast prove to be benign more often than malignancy. Most intracystic lesions are benign papillomas. Generally sizes of cysts that contain papilloma are small. Relatively cysts that contain papillary carcinoma are large. We present a 53-year-old with a papilloma in a large cyst of the breast that presented a painless palpable mass. Excisional biopsy may be needed to make a proper diagnosis for the suspicious lesion. Abstract: Introduction: Intracystic lesions of the breast prove to be benign more often than malignancy, most intracystic lesions are benign papillomas. Generally sizes of cysts that contain papilloma are small. Relatively cysts that contain papillary carcinoma are large. A papilloma in a large cyst of the Breast is rare. Presentation of case: We report a rare case of a papilloma in a large cyst of the breast that presented a painless palpable mass. A 53-yr-old woman noticed palpable mass in her right breast. Ultrasonography indicated a 7 × 7 cm sized large cyst. There is a 2 × 2.5 cm sized hyper-echoic, polypoid mass in the cyst. On fine-needle aspiration was not obtained malignant cells. Excisional biopsy was done. Pathologic finding was papilloma. Discussion: Tumors in a large cyst of the breast is difficult in distinguish benign from malignancy by preoperative imaging, cytological and histological study. Conclusion: Excisional biopsy should be performed before cancer surgery such as mastectomy to manage the cysts with intracystic growths.